2009
DOI: 10.1016/j.neuron.2009.09.040
|View full text |Cite
|
Sign up to set email alerts
|

An Automatic Valuation System in the Human Brain: Evidence from Functional Neuroimaging

Abstract: According to economic theories, preference for one item over others reveals its rank value on a common scale. Previous studies identified brain regions encoding such values. Here we verify that these regions can valuate various categories of objects and further test whether they still express preferences when attention is diverted to another task. During functional neuroimaging, participants rated either the pleasantness (explicit task) or the age (distractive task) of pictures from different categories (face,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

53
330
5
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(408 citation statements)
references
References 52 publications
53
330
5
3
Order By: Relevance
“…In some cases, but not all (23), a value-difference signal suggests a value comparison process within the ventromedial frontal cortex. On the other hand, an automatic ventromedial frontal valuation signal is found even when stimuli are presented in the absence of any decision requirement (24). The present finding that animals were beguiled into making incorrect choices, partly as a function of how much better V2 was than V3 and distracted by high values of V3 (Fig.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…In some cases, but not all (23), a value-difference signal suggests a value comparison process within the ventromedial frontal cortex. On the other hand, an automatic ventromedial frontal valuation signal is found even when stimuli are presented in the absence of any decision requirement (24). The present finding that animals were beguiled into making incorrect choices, partly as a function of how much better V2 was than V3 and distracted by high values of V3 (Fig.…”
Section: Discussionsupporting
confidence: 44%
“…S6). Medial OFC value signals, even if automatically generated (24), instead appear to be critical for guiding decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Positive correlation between activity and the values of chosen options and negative correlations with values of rejected options suggests a role in decision making (21) or attentional selection (23). However, there is also evidence the vmPFC tracks values of items even in the absence of any decision or when watching somebody else choosing (24,25). Some studies have suggested that these value representations are independent of reward type (money, food) (26) and reflect the impact of other Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike our current understanding of the valuation process for self-regarding choices (3,(6)(7)(8)(9)(10)(11)(12), it is much less clear whether learning also can be driven by other-regarding values, and whether this other-regarding valuation relies on the same mechanisms of reinforcement learning as those used for self. Moreover, despite the rapidly accumulating research on reward processing in social domains (13)(14)(15)(16)(17)(18)(19), the question remains of how neural representation of self-regarding vs. other-regarding values is related to individual differences in altruistic behavior.…”
mentioning
confidence: 87%